G20 and Global Governance: Catalyzing Cooperation, Sustainability, and Inclusive Development in the 21st Century (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Group of Twenty (G20) plays a crucial role in shaping the modern global order. As an intergovernmental forum composed of the world's largest economies, the G20 is instrumental in ensuring global economic and financial stability, advancing sustainable development, combating climate change, and promoting digital transformation. This paper delves into the purpose of the G20, its evolving scope, its achievements under India’s 2023 Presidency, and the broader significance of India’s role. Special emphasis is placed on policy coordination, inclusive growth, and the innovative role India played in expanding global cooperation. The G20 is not merely a diplomatic summit but a transformative platform that redefines multilateralism in a fragmented world.